2015
DOI: 10.1016/j.sbspro.2015.01.132
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Therapeutic Regime in Person with Type 2 Diabetes

Abstract: Background: It is expected that people with diabetes, throughout their lives, integrate and initiate a range of behavioral, therapeutic or preventive actions, suggesting the confirmed risk of occurring a globalized noncompliance, deteriorating their quality of life and an exponential economic impact. Objectives: to determine adherence to prescribed therapeutic regimen; and identify sociodemographic, clinical and psychosocial variables that influence adherence to the therapy. Methods: Was conducted a study quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
3
11
1
2
Order By: Relevance
“…Furthermore, contrary to the current finding, a previous study by Parajuli et al found that male participants adhered more to their MD than female ones did [38]. Although marital status had no significant association with adherence to MD in our research, Albuquerque et al's research found that being single had high a correlation with adherence to MD amongst patients with diabetes [39]. As well as contributing factors for non-compliance with diet, Parajuli et al's research included divorced status, negative family history of diabetes mellitus, and low knowledge of diabetes mellitus [38].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, contrary to the current finding, a previous study by Parajuli et al found that male participants adhered more to their MD than female ones did [38]. Although marital status had no significant association with adherence to MD in our research, Albuquerque et al's research found that being single had high a correlation with adherence to MD amongst patients with diabetes [39]. As well as contributing factors for non-compliance with diet, Parajuli et al's research included divorced status, negative family history of diabetes mellitus, and low knowledge of diabetes mellitus [38].…”
Section: Discussioncontrasting
confidence: 99%
“…Comparable to Kasznicki et al study where females constituted 62% and males 38% of type 2 diabetic patients. 8 In the present study currently married were 72.8%., similar to the study by Albuquerque et al 9 In the present study most of the subjects were illiterates 40%, followed by middle school 31.4%. In a study by Arulmozhi et al 39.3% had studied up to primary education level.…”
Section: Discussionsupporting
confidence: 93%
“…development of strategies, so this becomes the main manager of their illness. 2 The lack of positive attitude could be an important obstacle for long term management of diabetes. There is a need to increase knowledge and built positive attitude regarding diabetes and its complications as it has significant benefits including increase in adherence to treatment, thereby decreasing the complications associated with diabetes.…”
mentioning
confidence: 99%
“…O uso de práticas educativas como estratégia no tratamento de diabetes tipo 2 leva à melhora no conhecimento sobre a doença e o tratamento, além de motivar e reforçar a importância do estilo de vida, melhorando a qualidade de vida dos pacientes por meio do aumento de sua autonomia, adesão e, assim, capacitar no manejo da enfermidade. Pacientes com esse conhecimento conseguirão reconhecer a importância da adesão à farmacoterapia e o controle deste agravo à saúde (45).…”
Section: Contextualização Do Agravo à Saúde: Diabetes Tipounclassified